An Analytical Study of the Impact of Liquidity on the Economic Performance of Traditional Insurance Companies in Syria Using Panel Data Models (Journal of Hama University, 2025)
This study aims to analyze the impact of liquidity ratios on the economic performance of traditional insurance companies in Syria. The study covers traditional insurance companies in Syria during the period from 2013 to 2022, with financial data collected from the annual reports published on the website of the Insurance Supervisory Authority.The study employs a methodology of data analysis using Panel Data models to understand the influence of liquidity ratios on the economic performance of traditional insurance companies in Syria.The study adopted a data analysis methodology using Panel Data models to understand the impact of liquidity ratios on the economic performance of traditional insurance companies in Syria.The research concluded that liquidity ratios have a statistically significant impact on the economic performance of traditional insurance companies in Syria. Furthermore, there are no significant differences among traditional insurance companies in Syria. However, there is randomness in the behavior of traditional insurance companies in the process of liquidity management, which affects economic performance.An econometric model has been established to determine the effect of liquidity on the economic performance of traditional insurance companies in Syria, based on Panel EGLS with Period SUR model.
Keywords: Insurance companies; Economic Performance; Liquidity Ratios; Panel Data Models